Analysis, Design and Implementation of a Digital Marketing Strategy for Ecommerce - Sukandar, Bernhart Farras; Galinium, Maulahikmah; Mukadis, Panji (Journal of Applied Information, Communication and Technology, 2017)
This paper is an Analysis, Design and Implementation of a Digital Marketing Strategy for eCommerce. Marketers are faced with new challenges and opportunities within this digital age. Digital marketing is the utilization of electronic media by the marketers to promote the products or services into the market. The main objective of digital marketing is attracting users and allowing them to interact with the brand through digital media. This article focuses on the importance of digital marketing for both marketers and consumers. We examine the effect of digital marketing on MerekIndonesia.com. This study has described multiple channels of digital marketing, effectiveness of it and the impact it has on MerekIndonesia.com visitor. The examined sample consists of six digital marketing channel to prove the effectiveness of digital marketing. Collected data has been analyzed with the help of various statistical tools and techniques.